Controlling nucleation and growth of metal halide perovskite thin films for high-Efficiency perovskite solar cells - Sakai, N; Wang, Z; Burlakov, V; Lim, J; McMeekin, D; Pathak, S; Snaith, H (Wiley, 2017)
Metal halide perovskite thin films can be crystallized via a broad range of solution-based routes. However, the quality of the final films is strongly dependent upon small changes in solution composition and processing parameters. Here, this study demonstrates that a fractional substitution of PbCl2 with PbI2 in the 3CH3 NH3 I:PbCl2 mixed-halide starting solution has a profound influence upon the ensuing thin-film crystallization. The presence of PbI2 in the precursor induces a uniform distribution of regular quadrilateral-shaped CH3 NH3 PbI3 perovskite crystals in as-cast films, which subsequently grow to form pinhole-free perovskite films with highly crystalline domains. With this new formulation of 3CH3 NH3 I:0.98PbCl2 :0.02PbI2 , this study achieves a 19.1% current-voltage measured power conversion efficiency and a 17.2% stabilized power output in regular planar heterojunction solar cells.